2008
DOI: 10.1007/s00774-008-0861-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ghrelin, adiponectin, and leptin on bone mineral density in healthy postmenopausal women

Abstract: The association of body fat mass (FM) with bone mineral mass (BMC) and bone mineral density (BMD) has been attributed to a mechanical load exerted on the skeleton by FM and by the effect of different hormones. The aim of the present study was to determine whether there is a relationship between ghrelin, adiponectin, and leptin with BMC and BMD in healthy postmenopausal women (n = 88; age, 68.9 +/- 6.8 years; body mass index, 27.4 +/- 3.6 kg/m(2)). Body composition, BMC, and BMD were derived by dual-energy X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 46 publications
8
71
0
6
Order By: Relevance
“…The role of the insulin resistance still is quite controversial in the literature (30)(31)(32). One important issue that needs to be explored is that the association observed in the present investigation was only confirmed in boys.…”
Section: Discussionmentioning
confidence: 63%
“…The role of the insulin resistance still is quite controversial in the literature (30)(31)(32). One important issue that needs to be explored is that the association observed in the present investigation was only confirmed in boys.…”
Section: Discussionmentioning
confidence: 63%
“…In crosssectional studies, higher serum adiponectin has been generally associated with lower bone mineral density (BMD) values in premenopausal women, (8)(9)(10)(11) postmenopausal women, (10,12) and in women with the metabolic syndrome. (13,14) In one study, the association between serum adiponectin and BMD observed in postmenopausal women was not evident in premenopausal women. (15) Correlations have usually been weak, suggesting that adiponectin explained only a small component of the variance in ORIGINAL ARTICLE…”
Section: Introductionmentioning
confidence: 98%
“…On the day of mechanical testing, tibiae were thawed in 228C PBS for at least 1 h. Tibial length was measured (^0·01 mm) using digital callipers (Model 14-648-17, Fisher Scientific, Ottawa, ON, Canada). When each specimen was thawed, the round-surfaced cross head probe of a servo-controlled electromechanical testing system (Model 1122, Instron Corp., Canton, MA, USA) contacted the medial tibial surface at its longitudinal midpoint, between a 6 mm loading span (2,24,25) . Testing order was stratified based on dietary cohort, and load was applied at 0·17 mm/s (1,25) with a 50 kg compression load cell (Instron 2511-203; Instron Corp., Canton, MA, USA) until failure.…”
Section: Mechanical Testing: Three-point Bendingmentioning
confidence: 99%
“…When each specimen was thawed, the round-surfaced cross head probe of a servo-controlled electromechanical testing system (Model 1122, Instron Corp., Canton, MA, USA) contacted the medial tibial surface at its longitudinal midpoint, between a 6 mm loading span (2,24,25) . Testing order was stratified based on dietary cohort, and load was applied at 0·17 mm/s (1,25) with a 50 kg compression load cell (Instron 2511-203; Instron Corp., Canton, MA, USA) until failure. Load-deformation curves were digitised (200 Hz; Dataq Instruments, DI-730 Series, Akron, OH, USA), and structural properties such as tibial maximal load, load at proportional limit and energy to failure were determined.…”
Section: Mechanical Testing: Three-point Bendingmentioning
confidence: 99%